PENGEMBANGAN MODEL MOTIVATION BOOK (MOTIBOO) DALAM RANGKA PENINGKATAN MOTIVASI : SEBUAH PENELITIAN DAN PENGEMBANGAN (R&D) TERHADAP KARYAWAN LEMBAGA PENGEMBANGAN PERBANKAN INDONESIA - Hegar Harini (Jurnal Manajemen Pendidikan, 2014)
The model of Motivation Book (MOTIBOO) is a literature that focused on the employee motivation, which developed by Borg and Gall, (1983).The purpose of this study is to give more contribution on the field of knowledge of motivation, and gain the practical experience on the employee motivation.This study employeed the methodology that used by Borg and Gall to analysed the motivation. It consisted of four stages : 1) pre research; 2) planning; 3) development, field analysis, model test review and; 4) post research. I picked this model, as the objective of study which analysed the motivation of IBI employees. Closely relates to the method of Borg and Gall, it also gave more flexible measurement to observe the employee attitude to perform their works.This analys resulted the data that MOTIBOO can be used as an alternative method in order to improve the employee motivation in IBI, and it can increase the employee performance.